Sistema De Identificación Y Detección De Minas Antipersona “Detecboom” (2022)
Taking into account the current context of the country in which we are going through a post-conflict situation and that as a result of this irregular war in the national territory there is a problem with the minefields that were generated over 50 years, this is evident on the maps provided by the Agustín Codazzi Geographic Institute (IGAC), 2010